Low Ethanol Concentrations Promote Endothelial Progenitor Cell Capacity and Reparative Function - Lars Brodowski; Bianca Schröder-Heurich; Berina Kipke; Cara Schmidt; Constantin S. von Kaisenberg; Frauke von Versen-Höynck (Cardiovascular Therapeutics)
Background. Endothelial progenitor cells (EPCs) are recruited to injured endothelium and contribute to its regeneration. There is evidence that moderate ethanol consumption prevents the development and progression of atherosclerosis in a variety of in vitro and in vivo models and increases the mobilization of progenitor cells. Furthermore, there are studies that identified ethanol at low concentration as a therapeutic tool to mobilize progenitor cells in peripheral blood. At the same time, the cell number of EPCs represents a close link to cardiovascular system constitution and function and contributes to cardiovascular risk. The aim of this study was to evaluate the effect of low dose ethanol on typical features of endothelial colony-forming cells (ECFCs), a proliferative subtype of EPCs. Methods and Results. We tested whether ethanol impacts the functional abilities of ECFC (e.g., migration, tube formation, and proliferation) using in vitro assays, the intercommunication of ECFC by exploring cell surface molecules by flow cytometry, and the expression of (anti-)angiogenic molecules by ELISA. Low concentrations of ethanol concentration promoted migration, proliferation, and tubule formation of ECFC. The expression of the cell surface marker VE-cadherin, a protein which plays an important role in cell-cell interaction, was enhanced by ethanol, while (anti-)angiogenic molecule expression was not impacted. Conclusion. Ethanol at moderate concentrations increases the angiogenic abilities of endothelial progenitor cells thus possibly contributing to vasoprotection.